How green credit affects corporate environmental information disclosure: evidence from new energy listed companies in China - Geng, Limin; Yin, Wenxin; Wu, Xiaoxia; Lu, Xueyuan; Zhang, Can (Frontiers in Ecology and Evolution, 2023)
Environmental information disclosure is an important means to protect the ecological environment, and global climate change puts forward higher requirements for corporate environmental information disclosure. New energy companies play an important role in addressing climate change and environmental information disclosure, and should strengthen environmental information disclosure and actively participate in ecological environmental protection. This paper selected Chinese new energy listed companies as the research sample to investigate the impact of green credit on corporate environmental information disclosure, and proposed and empirically tested the hypothesis on the mechanism of the effect of green credit on environmental information disclosure. The regression results indicated that green credit can effectively improve the quality of corporate environmental information disclosure, and this conclusion is still significantly valid after robustness test; The impact mechanism tests showed that green credit can change the level of corporate environmental information disclosure by controlling company size. This paper also tested the heterogeneity and adjustment effects, showing that the relationship between green credit and environmental information disclosure are affected by multiple factors. Finally, this paper puts forward policy suggestions on how relevant companies and government regulatory departments can improve the quality and enthusiasm of corporate environmental information disclosure through the implementation of green credit, and how to strengthen the climate information disclosure of listed companies to improve the ecological environment.